1975
DOI: 10.1128/aac.7.5.614
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Antibiotic and Heavy Metal Resistance in Bacteria: Resistance Patterns in Staphylococci Isolated from Populations Not Known to be Exposed to Heavy Metals

Abstract: Staphylococci were isolated from clinical specimens obtained from patients not known to be exposed to abnormal levels of heavy metals. The antibiotic and heavy metal resistance patterns of these strains were determined by using a disk diffusion test and computer sorting. Though not absolute, an association of resistance to mercury and tetracycline in coagulase-negative strains was found, in contrast to resistance to copper and penicillin in coagulase-producing strains. A high degree of correlation was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…MICs meaning the lowest metal concentration value at which the growth of bacteria is inhibited were tested by a modified disc diffusion technique, as previously described by Groves and Young (1975). Sterile, blank, paper sensitivity discs (5 mm diameter) were saturated with 10 μl of diluted metal solutions in the range of 50-2,000 mg L −1 and dried for 3 h at 26 • C. Each disk contained 50-100-250-500-750-1000-2000 mg L −1 of Ni, Cd, Pb and Zn to give a zone of inhibition.…”
Section: Determination Of Metal Susceptibilitymentioning
confidence: 99%
“…MICs meaning the lowest metal concentration value at which the growth of bacteria is inhibited were tested by a modified disc diffusion technique, as previously described by Groves and Young (1975). Sterile, blank, paper sensitivity discs (5 mm diameter) were saturated with 10 μl of diluted metal solutions in the range of 50-2,000 mg L −1 and dried for 3 h at 26 • C. Each disk contained 50-100-250-500-750-1000-2000 mg L −1 of Ni, Cd, Pb and Zn to give a zone of inhibition.…”
Section: Determination Of Metal Susceptibilitymentioning
confidence: 99%
“…A frequency of Hgr among hospital populations of staphylococci is reported to be 32%. There is a close association of the Hgr phenotype with tetracycline resistance, a lack of mannitol fermentation, and coagulase-positive phenotype (35). Staphylococci isolated from rural and urban populations of Iraq exposed and not exposed to heavy metals or antibiotics gave different results.…”
Section: Effects Of Hgs On Methylation Of Mercurymentioning
confidence: 99%
“…Sequences were trimmed using MEGA X (v.10.2.4) (Kumar et al, 2018), and identified using the Basic Local Alignment Search Tool (BLAST) 16S/ITS BLASTn function against the nr database (BLAST 2.11.0) (Altschul et al, 1990) (Table S8). HMR isolates were subsequently tested for growth on PYT80 with ampicillin, kanamycin, or erythromycin to determine prevalence of cross-resistance (Groves et al, 1975; Wang et al, 2021); strains forming visible colonies in the presence of antibiotics within 7 days were considered tolerant.…”
Section: Methodsmentioning
confidence: 99%